2017
DOI: 10.3233/jpd-160982
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Constipation and Irritable Bowel Syndrome in Parkinson’s Disease Patients According to Rome III Diagnostic Criteria

Abstract: Background: Gastrointestinal symptoms are one of the most common non-motor features of Parkinson’s disease (PD). Recently, a report from Taiwan revealed that irritable bowel syndrome (IBS) may be associated with an increased risk of developing PD; however, the prevalence of IBS in PD patients has not been fully evaluated. Rome III criteria are widely assessed with a questionnaire to determine functional gastrointestinal disorders.Objective: We assessed the prevalence of constipation and IBS in PD patients in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
32
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 21 publications
9
32
2
Order By: Relevance
“…Our study also corroborates the few reports of associations between PD and intestinal disease, with significantly more PD patients than controls in our cohort reporting a history of inflammatory bowel disease, irritable bowel syndrome, Crohn's disease, and/or colitis. The mechanisms responsible for this epidemiological overlap have not been determined.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study also corroborates the few reports of associations between PD and intestinal disease, with significantly more PD patients than controls in our cohort reporting a history of inflammatory bowel disease, irritable bowel syndrome, Crohn's disease, and/or colitis. The mechanisms responsible for this epidemiological overlap have not been determined.…”
Section: Discussionsupporting
confidence: 91%
“…In keeping with the well‐known connections between inflammatory stimuli and impairment of gut barrier function, intestinal permeability in PD correlates with levels of αSYN as well as indicators of oxidative stress . In addition, recent studies have reported significant coincidence of IBD or irritable bowel syndrome and PD . One study reported the most direct confirmation of intestinal inflammation in PD, finding increases in mRNA transcripts encoding 4 proinflammatory cytokines (tumor necrosis factor, interferon gamma, interleukin‐6, and interleukin‐1β) as well as 3 glial markers in colonic biopsies of PD patients compared with age‐matched healthy controls …”
mentioning
confidence: 67%
See 1 more Smart Citation
“…According to Rome III criteria, 36.5% of PD patients fulfilled the criteria for IBS or FC, but in this group IBS+ was actually more prevalent than FC. A recent Japanese study reported IBS criteria to be fulfilled in 17.0% and FC in 27.1% of PD patients . Moreover, 58.1% of PD patients in our study had symptoms of diarrhoea.…”
Section: Discussionsupporting
confidence: 53%
“…Based on this hypothesis, it has been suggested that αSyn aggregates may potentially spread from the gut (ENS) to the brain (CNS) as a prion‐like protein by cell‐to‐cell transfer . These assumptions seem to be consistent with the long‐reported nonmotor symptoms of PD patients, often occurring before the onset of motor symptoms, including olfactory impairment and gastrointestinal (GI) dysfunctions, such as constipation and colonic inflammation …”
Section: Microbiota‐gut‐brain Axismentioning
confidence: 85%